Investigating the influence of boron diffusion temperature on the performance of n-type PERT monofacial solar cells with reduced thermal steps - Hakim Korichi; Mohamed Kezrane; Ahmed Baha-Eddine Bensdira (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
This research work aims to optimise the fabrication of n-based PERT monofacial solar cells of p⁺nn⁺ structure, using a simplified process and standard-sized n-type Czochralski (Si-Cz) monocrystalline silicon wafers. The aim is to achieve a conversion efficiency of 14.3%, comparable to the best performances reported for similar architectures. The study focused on the influence of the boron diffusion temperature on the emitter sheet resistance and the electrical performance of the cells. A diffusion temperature of 970°C was found to be optimal, offering a good compromise between low sheet resistance and uniform boron diffusion. Surface passivation by a layer of silicon oxide, deposited by dry thermal oxidation at 900°C in a controlled oxygen atmosphere, minimised surface recombination. The incorporation of an 80nm-thick silicon nitride (SiNx) anti-reflection coating (ARC), combined with pyramidal surface texturing, significantly reduced reflectance and optimised the absorption of incident light. The best-performing n-base PERT monofacial solar cell showed a short-circuit current density (Jsc) of 36.8 mA/cm², an open-circuit voltage (Voc) of 635 mV, a form factor (FF) of 0.79 and a conversion efficiency of 14.3%. These promising results confirm the potential of n-based PERT monofacial solar cells to achieve high performance using a simplified manufacturing process and standard wafer sizes, paving the way for low-cost production.